2012
DOI: 10.7436/rbts-2012.03.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de Alongamentos pela Estratégia Lemniscata do Método GDS sobre o Perfil Energético em Acupuntura

Abstract: Resumo: Contextualização: O exercício físico é uma das maneiras de cultivar a saúde. O Ryodoraku é um recurso de eletrodiagnóstico utilizado na acupuntura para avaliar o equilíbrio energético dos meridianos. Objetivo: Avaliar as alterações energéticas dos meridianos de acupuntura através do eletrodiagnóstico Ryodoraku, após uma sequência de alongamentos estabelecida pela estratégia da lemniscata do método de cadeias musculares e articulares GDS. Métodos: A amostra foi composta por 45 voluntários sadios de ambo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…19 Regarding the training of the authors of the selected studies, physical therapy predominated (62.5%; n = 5), 10.15-19 followed by dentistry (25%; n = 2), 20-21 medicine (25%; n = 2), 16-19 biomedicine (12.5%; n = 1) 16 and physical education (12.5%; n = 1) .17 It is also noted that in 75% of the studies (n = 6) , the authors also had training in acupuncture / integrative medicine. 15,[17][18][19][20][21] Among the selected studies, 12.5% (n = 1) presented evidence level II20; 25.5% (n = 2) presented evidence level III, 10.18 and 62.5% (n = 5) presented evidence level VI. [15][16][17]19,21 A total of 317 subjects participated in the selected studies, ranging in age from 4 to 84 years, 65.6% women and 33.2% men.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Regarding the training of the authors of the selected studies, physical therapy predominated (62.5%; n = 5), 10.15-19 followed by dentistry (25%; n = 2), 20-21 medicine (25%; n = 2), 16-19 biomedicine (12.5%; n = 1) 16 and physical education (12.5%; n = 1) .17 It is also noted that in 75% of the studies (n = 6) , the authors also had training in acupuncture / integrative medicine. 15,[17][18][19][20][21] Among the selected studies, 12.5% (n = 1) presented evidence level II20; 25.5% (n = 2) presented evidence level III, 10.18 and 62.5% (n = 5) presented evidence level VI. [15][16][17]19,21 A total of 317 subjects participated in the selected studies, ranging in age from 4 to 84 years, 65.6% women and 33.2% men.…”
Section: Resultsmentioning
confidence: 99%
“…19 The clinical conditions of the volunteers were: onycholysis; 15 temporomandibular dysfunction; [20][21] fibromyalgia; 16 work-related musculoskeletal disorders; 17 and cystic fibrosis; 19 in addition to healthy people. 10,18 The characterization of the studies regarding the objectives, Ryodoraku measurement acupunctions, application method, energy profile according to TCM precepts and study conclusions are presented in Chart 1. Two studies [18][19] did not explain the pattern of the energy profile found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations